Hábito de estudio y rendimiento académico en estudiantes de la Escuela Académica Profesional de Idiomas de la Universidad Nacional de San Martín 2007 - Torres Torres, Elmira del Rosario (2009)
The research paper had as major aim to know the influence of the habit of study on the academic performance from students of Languages in the UNSM, 2007- II, II cycle to 2008-I, III cycle. For that reason, we had to analyze and compare the habit of study that the students have in both moments of the research; which was gathered by the application of the questionnaire. We analyzed and compared the academic performance, as well. To gather the results, we used different survey techniques with their own instruments of measuring, such as: Documental observation, poll. In addition, we used techniques of processing the data, which allowed us to review, classify, codify and tabulate the information. By the coefficient of correlation and the T-student dispersion, we proved the hypothesis of research. In this way, we concluded the habit of study influences mainly on the academic performance from the students of the Language Academic Professional School in the National University of San Martin, 2007-II, II cycle to 2008-I, III cycle.